Puff Pastry Substitusi Komposit Ikan Bawal Dan Daun Kol Banda Puff Pastry Composite Substitution Of Pomfret And Pisonia Alba Leaf - Ira Handayani; Sabilla Aditya Prameswari (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2022)
Puff pastry is a crunchy textured food that has a fragile network of layers made from wheat flour. To anticipate the use of wheat flour, flour from local food ingredients such as pomfret flour and Pisona alba leaf flour can be used. Purpose of the research: 1) Knowing the level of public preference for puff pastry with composite substitution of pomfret flour and Pisonia alba leaf flour; 2) Knowing the composition of the best formula used in the manufacture of puff pastry composite substitution of pomfret flour and Pisonia alba leaf flour. The methods used in this research are the method of literature, experimentation, documentation, questionnaire, sensory testing, hedonic testing and data analysis. Pomfret flour and Pisonia alba leaf used as much as 5%, 10%, 15% of the weight of the flour. The results showed that puff pastry with pomfret flour and Pisonia alba leaf flour were the most preferred and accepted by the panelists as products with the composite substitution of pomfret flour and Pisonia alba leaf flour as much as 5%.